Enhancing Financial Sustainability in Notarial Services: Streamlined Processes Through Digitalization - Keizia Vitradijane Darmawan (Jurnal Impresi Indonesia, 2025)
This study investigates the impact of digitalization on operational efficiency and financial sustainability in Indonesian notarial services, focusing on Kantor Notaris Justriany Koni, S.H., M.Kn. The traditional manual systems in Indonesian notary offices result in rising operational costs, declining profit margins, and reduced client satisfaction. Using a case study approach, this research analyzes the financial and operational effects of partial digitalization in administrative, communication, and financial workflows—excluding core notarization acts restricted by law. A mixed-methods approach was employed, including stakeholder interviews, cost-benefit analysis, and comparative benchmarking. The findings demonstrate that strategic digital transformation can reduce document handling costs by up to 30%, increase service capacity without additional staffing, and improve cash flow through electronic invoicing. The study presents a hybrid implementation roadmap that aligns with existing regulations, balances investment risk, and ensures business continuity. The proposed digital solutions offer a scalable path for notarial offices seeking to modernize, remain competitive, and enhance long-term sustainability.